The first experience of combined treatment of brain malignant gliomas by means of blocking membrane calcium channels - Gridina, Nina Ya.; Zhebrivska, Filia I.; Morozov, Аnatoly M.; Rozumenko, Volodymyr D.; Ushenin, Yuri V.; Rozumenko, Аrtem V.; Shmeleva, Аnnа А.; Bilousova, Аnnа D.; Biloshytsky, Vadym V. (Ukrainian Neurosurgical Journal, 2019)
Objective. To investigate the antitumor effect of low concentrations of calcium channel blockers on the example of verapamil hydrochloride in the combined treatment of patients with glioblastomas after operation. Materials and methods. Patients who underwent brain tumor surgery, postoperative radiotherapy and chemotherapy were divided into two groups. The first group of 8 patients received verapamil hydrochloride at low concentrations; the second group (32 patients) served as a control group. The drug concentration was selected individually according to peripheral blood cells aggregation data on the “Plasmon-6” biosensor. The criterion for selecting the drug concentration was the lowest level of peripheral blood cells aggregation in vitro, reflecting the level of blocking of NMDA-dependent calcium channels on the membranes of peripheral blood cells. The optimal concentration of verapamil hydrochloride for all patients was less than 10,000 times less compared to common dose. The criteria of the antitumor activity of verapamil hydrochloride at low concentrations was the postoperative life expectancy of the patients. Results. When using the drug in patients, there were no signs of toxic effects of verapamil hydrochloride on the body, and life expectancy was 10 months more compared to the group of patients not treated with verapamil hydrochloride at low concentrations in the postoperative period. Conclusions. There was an increase in the life expectancy and improvement of the quality of life in patients who received treatment with low concentrations of verapamil hydrochloride, along with the absence of the toxic and tumor-stimulating action of the drug.